"Fathers without children" : a discursive study of the accounts and identities presented by sperm donors : a dissertation presented in partial fulfilment of the requirements for the degree of PhD in Psychology at Massey University, Tiritea, Palmerston North, New Zealand - Ross, Kirsty J. (Massey University, 2004)
Discursive psychology challenges traditional psychology by contending that knowledge, reality and the "truth" are socially constructed and actively negotiated through language. Through discourse, people are placed in, or adopt, subject positions and roles that confer certain rights and responsibilities. Current discourses for talking about sperm donors can be seen to negatively position them at a low status, with little power or rights, but multiple obligations. This research interviewed 24 New Zealand sperm donors, with the aim of investigating how donors constructed and made sense of their experiences and their position as a sperm donor. These discourses revealed that being a sperm donor can lead to an enhanced construction of masculinity, and an accompanying powerful subject position with regards to other men in society. This had ramifications for the donors' relationship with both the 'social father' and the biological mother of the offspring. Donors' discourses of fatherhood revealed a delicate balancing act of trying to claim a position of (biological) father, and establish a role and place within the lives of the offspring without encroaching on the position of the recipients as parents, particularly the male 'daddy'. Through their language and utilisation of discourses concerning masculinity and fatherhood, the men in this study challenged the dominant construction of sperm donors, and provided an alternative understanding of the psychology of being a sperm donor.
Keywords: Sperm donors; Fatherhood; Paternity; Masculinity